Peripheral neuropathy associated with subcutaneous or intravenous bortezomib in patients with newly diagnosed myeloma treated within the GMMG MM5 phase III trial - Merz, Maximilian; Mai, Elias K.; Bertsch, Uta; Hose, Dirk; Seckinger, Anja; Jauch, Anna; Hillengaß, Jens; Raab, Marc-Steffen; Schurich, Bärbel; Goldschmidt, Hartmut (Haematologica, 2016)
Up to 20% of patients with multiple myeloma (MM) show signs of peripheral neuropathy (PN) at primary diagnosis.[1][1] Treatment with neurotoxic agents such as bortezomib or thalidomide increases rates of PN in newly diagnosed patients by up to 50%.[2][2] Since subcutaneous (SC) administration